مدى مساهمة مبادئ حوكمة الشركات في تحسين جودة التقارير المالية - بن جدو ،أمينة; الحاج أحمد ،فوزي (جامعة الوادي University of Eloued, 2025)
This study aims to develop a structural model to assess the impact of implementing corporate governance principles, represented by three key dimensions: ensuring effective corporate governance, protecting stakeholders' rights, and enhancing disclosure and transparency, on the quality of financial reports. To achieve this, a questionnaire was used as a data collection tool, targeting a sample of executives at Condor Electronics in the Bordj Bou Arréridj province. The collected data was then analyzed using the statistical software SPSS and AMOS. The study's findings revealed a statistically significant positive relationship between the application of corporate governance principles and the quality of financial reports, highlighting the effective contribution of corporate governance in enhancing the credibility and reliability of financial reports.
The Extent of Corporate Governance Principles' Contribution to Improving the Quality of Financial Reports – A Case Study of Condor Electronics
Keywords: حوكمة الشركات; جودة التقارير المالية; نموذج هيكلي; مؤسسة كوندور إلكترونيكس; Corporate Governance; Financial Report Quality; Structural Model; Condor Electronics